Atomizing core body and preparation method and application thereof
By using short fiber slurry to create and perform wet pressure and dry pressure treatment, the problem of uneven distribution of pore size and porosity of the atomized core is solved, achieving a more uniform liquid conduction performance and a higher suction experience.
Patent Information
- Application Number
- CN202311283364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The pore size and porosity distribution of the existing atomized cores is uneven, resulting in poor liquid conduction performance and easy to cause layered drops during automated assembly.
The slurry containing short fibers is used to form an interwoven integrated atomized core structure. The fiber connection force is increased through wet and dry pressure steps, and the slurry treatment increases the fine fiber filaments on the fiber surface to improve the liquid locking capacity.
The pore size distribution of the atomized core is achieved more uniformly, and the liquid conduction performance is more consistent, which avoids the risk of layered drop, improves the contact efficiency with the heating body, and ensures a higher suction experience and consistent taste.
Smart Images

Figure BDA0004479024120000081 
Figure BDA0004479024120000091 
Figure BDA0004479024120000092
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electronic atomization, and in particular to an atomization core and a preparation method and application thereof. Background Art
[0002] The atomizer core in the prior art is mostly made of multi-layer non-woven fabrics through edge lamination. The multi-layer non-woven fabrics are made of long fibers. The long fibers have the following characteristics: (1) Long fibers have better liquid conductivity. The reason is that the long fibers are longer (1-5cm) and the gaps between the fibers are larger, so the liquid can flow more easily between the fibers. (2) The liquid can easily escape through the gaps between the fibers, resulting in weak liquid locking ability. At present, the liquid locking ability of multi-layer non-woven fabrics is mainly improved by increasing the gram weight, compressing the thickness, and interlacing the horizontal and vertical lines. (3) Long fibers usually have a larger porosity and a lower fiber density. This structure is conducive to the flow of liquid between the fibers and improves the liquid conductivity.
[0003] When multiple layers of spunlace nonwoven fabrics are stacked and bonded together to form an atomizer core, the pore size and porosity distribution of the core will be affected by many factors, including the pore size and porosity of each layer of spunlace nonwoven fabric, the number of stacked layers, the bonding method, etc. The increase in the number of stacked nonwoven fabric layers will lead to uneven distribution of the pore size and porosity of the core. For example, the pore size and porosity distribution of multiple layers of nonwoven fabrics are uneven due to inconsistent interlayer gaps. The uneven distribution of pore size and porosity will have some adverse effects on the liquid conduction performance, such as: (a) Poor liquid conduction path: Uneven distribution of pore size and porosity will lead to poor flow path of liquid in the material, hindering the liquid conduction performance of the liquid. Blocked or overlapping holes will form resistance to liquid conduction, making it difficult for the liquid to flow. (b) Uneven liquid conduction speed: Uneven distribution of pore size and porosity will lead to uneven flow speed of liquid in the material. This speed difference will affect the uniform distribution and permeability of the liquid in the material.
[0004] In addition, multi-layer non-woven fabrics are prone to the risk of delamination and falling during automated assembly after cutting. There are several main reasons: (1) Fiber structure: Multi-layer non-woven fabrics are usually made of multiple layers of fiber mesh, and the fibers are fixed by pressure. After cutting, due to the weak connection between the fibers, delamination is prone to occur. Especially in the automated assembly process, the effects of vibration, friction and other forces will further weaken the connection between the fibers, resulting in delamination and falling. (2) Edge treatment: During the cutting process, the edges of multi-layer non-woven fabrics usually need to be treated to prevent the fibers from loosening and delamination. If the edges are not properly treated or properly fixed, delamination and falling are prone to occur. (3) External force: During the automated assembly process, multi-layer non-woven fabrics may be subjected to external forces such as extrusion, stretching, friction, etc. These external forces will weaken the connection between the fibers, thereby increasing the risk of delamination and falling. Summary of the invention
[0005] In order to overcome the above problems in the prior art, one of the objectives of the present invention is to provide an atomizer core.
[0006] A second object of the present invention is to provide a method for preparing an atomizer core.
[0007] A third object of the present invention is to provide an atomizing device.
[0008] A fourth object of the present invention is to provide an application of an atomizer core in the field of electronic atomization.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides an atomizing core, wherein the atomizing core is an interwoven integrated structure formed by forming a slurry containing short fibers, and the atomizing core meets at least one of the following characteristics:
[0011] (1) The difference in liquid conduction rate between the atomizer core in the X-axis and the Y-axis is less than 10%, and the difference in liquid conduction rate between the atomizer core in the X / Y-axis and the Z-axis is less than 25%;
[0012] (2) The difference in thermal conductivity between the atomizer core in the X-axis and the Y-axis is less than 10%, and the difference in thermal conductivity between the atomizer core in the X / Y-axis and the Z-axis is less than 20%;
[0013] (3) 90% of the pore size of the atomizer core is 5μm <a<45μm,5μm<b<45μm,b-a≤5μm。
[0014] The particle size of the aerosol generated by the electronic cigarette has a certain relationship with the pore diameter, pore size distribution, and porosity of the atomization core. The pore size of the atomization core affects the penetration and diffusion ability of aerosol particles in the material. An atomization core with a larger pore size allows larger aerosol particles to pass through the core material more easily, while a smaller pore size can block the passage of larger aerosol particles. Compared with the atomization core made by laminating non-woven fabrics, the pore size distribution of the atomization core in the present invention is more uniform, and the pore size distribution of the atomization core affects the distribution and filtration effect of aerosol particles in the core material. If the pore size distribution range of the atomization core is wide, that is, the pore size sizes vary greatly, then aerosol particles of different sizes may exhibit different distribution situations in the core material, resulting in different degrees of obstruction for aerosol particles of different sizes when passing through the atomization core. Therefore, compared with the atomization core made by laminating non-woven fabrics, the atomization core in the present invention has a more uniform pore size and pore size distribution, the aerosol particle size atomized is more consistent, the particle size distribution is more concentrated, the consistency of TPM and nicotine release is better, the suction experience before and after is consistent, and there is no problem of flavor attenuation. In addition, the liquid conduction, heat conduction, and pore size distribution of the atomization core in the XYZ three-axis directions of the present invention have little difference. During subsequent processing and assembly, it can be directly cut or assembled without distinguishing the front and back sides of the material.
[0015] Preferably, the difference in the liquid conduction rate of the atomization core in the X-axis and Y-axis is less than 5%, and the difference in the liquid conduction rate of the atomization core in the X / Y-axis and Z-axis is less than 25%; more preferably, the difference in the liquid conduction rate of the atomization core in the X-axis and Y-axis is less than 4.3%, and the difference in the liquid conduction rate of the atomization core in the X / Y-axis and Z-axis is less than 25%.
[0016] Preferably, the difference in the thermal conductivity coefficient of the atomization core in the X-axis and Y-axis is less than 6%, and the difference in the thermal conductivity coefficient of the atomization core in the X / Y-axis and Z-axis is less than 20%.
[0017] Preferably, 90% of the pore diameters of the atomization core are 5μm < a < 45μm, 5μm < b < 45μm, b - a ≤ 4μm; more preferably, 90% of the pore diameters of the atomization core are 5μm < a < 45μm, 5μm < b < 45μm, b - a ≤ 3.1μm.
[0018] Preferably, the length of the short fibers is 5 - 13mm.
[0019] Preferably, the diameter of the short fibers is 10 - 30μm.
[0020] Preferably, the surface of the short fibers is distributed with fibrillated fiber filaments with a diameter of 0.01 - 0.5μm.
[0021] The mesh structure of short fibers provides more contact points for the contact between the atomizer core and the heating element, increases the contact area between the atomizer core and the heating element, and thus improves the heat conduction efficiency. Short fibers have a larger surface area than long fibers. Since the length of short fibers is shorter and the gaps between the fibers are smaller, the surface area of short fibers is larger. During the wetting process, the liquid can more easily penetrate the surface of the short fibers, causing them to wet and swell. The short fibers have better dispersion in the material and the contact between the fibers is closer. This dispersion allows the liquid to be more evenly distributed between the short fibers, thereby promoting the wetting and swelling of the short fibers. The reasons why short fibers are easier to swell than long fibers mainly include their larger surface area, smaller fiber gaps, uniform fiber shape, and good fiber dispersion. These factors enable short fibers to absorb liquid and swell more easily. Therefore, compared with long fibers, the atomizer core made of short fibers fits more closely with the heating element after swelling, and has better heat and liquid conduction effects. Compared with long fibers, the liquid conduction performance of the atomizer core made of short fibers is slightly worse, which avoids the occurrence of oil explosion caused by the small amount of smoke oil in the latter part, fast liquid conduction and thick oil film during the latter part of the inhalation.
[0022] Preferably, the liquid conducting rate of the atomizing core is 4 to 15 μL / s.
[0023] Preferably, the thermal conductivity of the atomizer core is 0.06-0.09 Wm -1 .K -1 .
[0024] Preferably, the oil holding rate of the atomizer core is 62-92%.
[0025] Preferably, the moisture regain of the atomizing core is 600-950%.
[0026] Preferably, the fiber density of the atomizing core is 50-400 kg / m 3 .
[0027] Preferably, the porosity of the atomizer core is 60-93%; further preferably, the porosity of the atomizer core is 85-90%. The porosity of the atomizer core refers to the ratio of the pore volume to the total volume. A higher porosity means that there are more spaces in the core material for aerosol particles to pass through. Therefore, a higher porosity may cause larger aerosol particles to pass through the material more easily.
[0028] Preferably, the pore size of the atomizer core is 5-100 μm. The porosity and pore size structure of the atomizer core in the present invention are between those of multi-layer non-woven fabrics and ceramics, and has the advantages of both cotton cores and ceramic cores, thus realizing ceramic cotton core.
[0029] Preferably, the thickness of the atomizer core is 1 to 4 mm.
[0030] Preferably, the average pore size of the atomizing core is 11-18 μm.
[0031] Preferably, the D90 value of the atomizer core is 10.9-16.3 μm.
[0032] The second aspect of the present invention provides a method for preparing the atomizer core provided by the first aspect of the present invention, comprising the following steps:
[0033] The short fibers are beaten, then formed into sheets, and then wet pressed, dried, and dry pressed in sequence to obtain the atomizing core.
[0034] The present invention adopts wet pressing and dry pressing steps, which can reduce the gap between the fiber of the atomizer core and the heating element, reduce the presence of air or other media between the heating element and the atomizer core, further improve the heat conduction efficiency, ensure better heat conduction, and reduce the risk of poor heat conduction between the heating element and the atomizer core, such as reducing the risk of core sticking, oil leakage and oil explosion. The present invention uses beating to treat short fibers, so that the surface of the short fibers is divided and broomed to form a large number of fine fibers, forming a certain resistance to the liquid conduction path, thereby achieving the purpose of improving the liquid locking ability. The atomizer core in the present invention is composed of short fibers, and the liquid conduction ability is relatively weak, but it has a good liquid locking ability; especially after the short fibers are beaten and divided and broomed (the degree of division and brooming is related to the beating parameters, such as: beating pressure, beating speed frequency, etc.), many fine fibers are formed on the surface of the short fibers, which enhances the connection between the short fibers in the atomizer core, improves the overall strength of the material, and at the same time creates a certain obstacle to the flow of the liquid, thereby improving the liquid locking ability.
[0035] Preferably, in the beating step, the beating pressure is 0.4-0.6 MPa.
[0036] Preferably, in the beating step, the beating speed frequency is 35 to 45 Hz; further preferably, the beating speed frequency is 38 to 42 Hz.
[0037] Preferably, in the beating step, the beating degree is 25 to 26 degrees; more preferably, the beating degree is 25.3 to 25.8 degrees; even more preferably, the beating degree is 25.4 to 25.6 degrees.
[0038] Preferably, in the beating step, the beating concentration is 0.6-0.7%; more preferably, the beating concentration is 0.66-0.68%.
[0039] Preferably, in the beating step, the beating time is 60 to 70 minutes.
[0040] Preferably, the papermaking molding step comprises: injecting the pulped slurry into a molding machine, bubbling, then dehydrating, and evacuating.
[0041] Preferably, the injection height of the slurry is 20 to 25 cm.
[0042] Preferably, the bubbling time is 18 to 25 seconds.
[0043] Preferably, the dehydration time is 50 to 90 seconds.
[0044] Preferably, the vacuuming time is 10 to 40 seconds.
[0045] Preferably, in the wet pressing step, the wet pressing pressure is 0-200 N / m and the thickness is 1.0-2.0 mm.
[0046] Preferably, in the dry pressing step, the dry pressing pressure is 0-200 N / m and the thickness is 1.0-2.0 mm.
[0047] The specific parameters of dry pressing and wet pressing in the present invention need to be adjusted according to the gram weight and thickness of the atomizer core. The main function of wet pressing and dry pressing is to shape the surface, flatten the raised fiber part, and make the surface smooth. By adjusting the appropriate pressure, the final sample reaches the target thickness.
[0048] Preferably, the drying step is pre-freeze drying and then freeze drying.
[0049] Preferably, in the pre-freeze-drying step, the pre-freezing temperature is -28 to -35°C.
[0050] Preferably, in the pre-freeze-drying step, the pre-freezing time is not less than 2 hours.
[0051] Preferably, in the freeze-drying step, the vacuum degree is less than 30Pa.
[0052] Preferably, the freeze-drying step is specifically as follows: first freeze-drying at -28 to -35°C for 10 to 15 hours, and then heating to 20 to 30°C for drying for 10 to 15 hours. In the present invention, the freeze-drying step is used to better maintain the stability of the pore size and porosity of the produced atomizer core during the drying process. If a drying process is used, the atomizer core will shrink and the pore size will become smaller.
[0053] The third aspect of the present invention provides an atomization device, comprising the atomization core provided by the first aspect of the present invention.
[0054] The fourth aspect of the present invention provides the application of the atomizer core provided by the first aspect of the present invention in the field of electronic atomization.
[0055] The beneficial effects of the present invention are: the pore size distribution of the atomizer core in the present invention is uniform and concentrated, which is conducive to better transmission of the atomized liquid. When the pore sizes are close, the dynamic behavior of the atomized liquid transmission is more consistent, thereby providing a higher and more uniform atomized liquid transmission efficiency; and because the atomizer core is an integrated structure, there will be no fiber stratification or chipping problems during subsequent processing. The atomizer core in the present invention has small differences in liquid conduction capacity and thermal conductivity in the XYZ three-axis direction. When applied to an atomizer device, problems such as core sticking, oil leakage, and oil explosion can be avoided. In addition, compared with the atomizer core made of non-woven fabric laminates, the pore size and pore size distribution of the atomizer core in the present invention are more uniform, the particle size of the aerosol particles formed by atomization is also more uniform, the suction effect and taste are better, and there is no problem of taste attenuation.
[0056] The present invention forms a porous structure by wet-molding short fibers, thereby giving the atomizer core a stable shape and size, and then through wet pressing and dry pressing, the thickness consistency is good, the surface flatness is good, and the atomizer core has a low rebound after wetting or compression, so that the atomizer core can fit more closely with the heating element, avoiding damage to the heating element due to dry burning. In addition, the short fibers are separated and formed on the surface of the short fibers through pulping, which enhances the bonding force and stability between the short fibers in the atomizer core, improves the overall strength of the atomizer core, and in the subsequent processing, there is no risk of delamination or chipping, and at the same time, it creates a certain hindrance to the flow of the liquid, thereby improving the liquid locking ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a scanning electron microscope image of the atomizer core in Example 1.
[0058] Figure 2 This is a physical picture of the atomizer core in Example 1.
[0059] Figure 3 The present invention is a flow chart of the preparation process of an embodiment of the present invention.
[0060] Figure 4 This is a scanning electron microscope image of the atomizer core in Comparative Example 1.
[0061] Figure 5 This is an optical microscope magnified image of the atomizer core in Comparative Example 1.
[0062] Figure 6 It is an XYZ three-axis schematic diagram of the atomizer core in an embodiment of the present invention.
[0063] Figure 7 Schematic diagram of the overall structure of the liquid conduction performance testing device.
[0064] Figure 8 This is a schematic diagram of the structure of the transparent upper plate and the transparent lower plate of the liquid conduction performance testing device.
[0065] Fig. 9 It is a test result diagram of the liquid conducting performance of the atomizer core on the X-axis and Y-axis in Examples 1 to 6 of the present invention and Comparative Examples 1 to 6.
[0066] Fig.10 The figure is a test result diagram of the liquid guiding performance of the atomizer core in Examples 1 to 6 of the present invention and Comparative Examples 1 to 6 on the X-axis and Z-axis.
[0067] Fig.11 The figure is a test result diagram of the liquid guiding performance of the atomizer core in Examples 1 to 6 of the present invention and Comparative Examples 1 to 6 on the Y-axis and Z-axis.
[0068] Fig.12 This is a test diagram of the pore size and pore size distribution of the atomizer core in the present invention. DETAILED DESCRIPTION
[0069] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0070] Examples 1 to 6
[0071] The atomizer core in Examples 1 to 6 is an interwoven integrated structure formed by papermaking of natural refined cotton linter pulp, and the thickness of the atomizer core is 1.3 to 2.0 mm; the fiber length of natural refined cotton linter is 5 to 13 mm, the fiber diameter is 10 to 30 μm, and fine fiber filaments formed by brooming are distributed on the fiber surface, and the fiber filaments have a diameter of 0.01-0.5 μm. In the atomizer core, the fibers in the natural refined cotton linter are interwoven to form an integrated structure, and the fiber filaments on the fiber surface are also interwoven, which further improves the degree of interweaving between the fibers of the atomizer core, avoids the occurrence of delamination and falling of the atomizer core during cutting and processing, and improves the liquid conduction rate. Among them, the scanning electron microscope image of the atomizer core in Example 1 is as follows: Figure 1 As shown, Figure 1 (a) and Figure 1 (b) SEM images of the atomizer core with scales of 1 mm and 100 μm, respectively. Figure 1 It can be seen that the fibers in the atomizer core are intertwined with each other, and many fine fiber filaments formed by brooming are distributed on the fiber surface, and the fiber filaments on different fibers are intertwined with each other. Figure 2 As shown, Figure 2 (a) is a 50-fold magnification of the atomizer core surface; Figure 2 (b) is a real picture of the atomizer core.
[0072] The bubble point method was used to test the average pore size of the atomizer cores in Examples 1 to 6, and the capillary drop method was used to test the liquid conduction rate. The liquid conduction rate obtained by the test reflects the comprehensive liquid conduction performance of the atomizer core in three directions of XYZ. The gram weight, thickness, pore size, porosity, oil holding capacity and liquid conduction rate of the atomizer cores in Examples 1 to 6 are shown in Table 2, respectively.
[0073] Reference Figure 3 The atomizer cores in Examples 1 to 6 are prepared by the following preparation method, which specifically includes the following steps:
[0074] 1. Beating: Pour an appropriate amount of pure water into the beater, and then weigh a short fiber sample of appropriate weight (the amount of the sample is calculated according to the volume of the former and the fiber density of the atomizing core), soak and evenly disperse it into the beater, control the beating concentration at 0.67% ± 0.01%, set the beating parameters, the beating pressure is 0.5Mpa, the beater speed frequency is 40Hz, the beating time is 60-70 minutes (adjust according to the beating degree, control the beating degree to 25.5 ± 1 degrees), turn on the beater, run it for 5 minutes without pressure to loosen it, and then start beating;
[0075] 2. Forming: The forming equipment mainly includes: grouting pump, former, forming mesh, vacuum system, control system, etc. After beating, turn on the delivery pump to pump the beating liquid into the slurry tank, add water to dilute it from the beating machine according to the quantitative or required concentration, and then start the machine for stirring. Usually, stirring for 5-10 minutes is required before forming; the grouting liquid level is generally controlled at 15-30cm (the area of the forming mesh is 42cm*42cm, the slurry concentration is constant, and the grouting liquid level height is controlled for quantitative determination), and the liquid level sensor height is adjusted according to the quantitative height; the bubbling time is set to 20s, and the grouting pipe is lifted and left to stand for 1s before dehydration. The dehydration time is generally controlled at 70±20s, and the vacuum time is generally controlled at 10-40s. The vacuum time can be adjusted according to the actual situation;
[0076] 3. Wet pressing: adjust the pressure and speed of wet pressing according to the thickness and surface flatness. Wet pressing parameters: pressure 0-200N / m, thickness 1.3-2.5mm, and obtain the sheet;
[0077] 4. Pre-freeze drying: The temperature of the cold storage is set to -30℃, and the freezing time of the slices after they are transferred into the cold storage is not less than 2 hours;
[0078] 5. Freeze drying: When transferring the sheets from the cold storage to the freeze dryer, the retention time of the sheets at room temperature should be minimized to prevent ice from melting; after transferring the sheets to the freeze dryer, the freeze drying program is run. The specific freeze drying program is: keep at -30℃ for 12 hours, then rise to 25℃ and keep for 12 hours to complete the freeze drying of the sample; after the freeze drying program is completed, take out the sample to check whether it is completely dry; the absolute vacuum degree of the freeze dryer should be <30Pa, and the freeze drying program is run according to the set program. The relationship between freeze drying time and fiber weight is shown in Table 1;
[0079] 6. Dry pressing: the pressure and speed of dry pressing were adjusted according to the thickness and surface flatness. The dry pressing parameters were as follows: pressure 0-200 N / m, thickness 1.3-2.0 mm, and the atomizer cores in Examples 1 to 6 were obtained respectively.
[0080] Table 1 Relationship between freeze-drying time and fiber weight
[0081] <![CDATA[Grammage (g / m 2 )]]> <150 150-180 180-220 220-250 250-280 Freeze drying time (h) 15 16 17 18 19
[0082] Comparative Examples 1 to 6
[0083] The atomizer cores in Comparative Examples 1 to 6 are made of laminated non-woven fabrics, and the gram weight, thickness, pore size, porosity, oil holding and liquid conduction rates of the atomizer cores are shown in Table 2, respectively.
[0084] When preparing the atomizer cores in Comparative Examples 1 to 6, the long fiber mixture is processed through a pre-stimulation device to increase the looseness of the fibers and the cross-linking between the fibers; then a high-speed water jet is used to impact the cotton fibers to make the fibers entangled with each other. The water jet pushes and penetrates the fibers into the cloth layer, so that the fibers are intertwined and entangled with each other to form a compact non-woven fabric layer structure; then multiple layers of non-woven fabrics are laminated, and the number of layers of non-woven fabrics used when laminating the atomizer core is determined according to the thickness of the atomizer core. When laminating, the horizontal and vertical lines are laminated crosswise to increase the liquid conduction performance, and finally molded and cut into installed size samples. The preparation method of the atomizer core in Comparative Examples 1 to 6 has a relatively cumbersome operation process and low efficiency.
[0085] The atomizer cores in Comparative Examples 1 to 6 are made of multiple layers of non-woven fabrics, which are then pressed and cut. They have the following disadvantages: (1) The cutting process is complicated, and before cutting, it needs to go through cutting, lamination, watering, and final mold pressing and cutting, which is inefficient; (2) There is a risk of delamination during the cutting and assembly processes, which affects product quality and consistency of the smoking experience; (3) Cutting multiple layers of non-woven fabrics will form gaps between layers, affecting the oil conduction rate. The atomizer core in the present invention does not have the above problems.
[0086] Comparative Example 1: The scanning electron microscope image of the atomizer core made of multi-layer non-woven fabric is as follows Figure 4 As shown, the optical microscope magnified image is as follows Figure 5 As shown, Figure 4 (a) Figure 4 (b) and Figure 4 (c) SEM images with scales of 1 mm, 100 μm, and 500 μm, respectively. Figure 4 and Figure 5 It can be seen that there are no fine fiber filaments on the fiber surface in Comparative Example 1.
[0087] Table 2 Performance parameters of the atomizer core in Examples 1 to 6 and Comparative Examples 1 to 6
[0088]
[0089]
[0090] It can be seen from Table 2 that with the increase of fiber weight (from 140g / m 2 Increased to 280g / m 2 ), the porosity of the atomizer core gradually decreases (from 89% to 85%), the oil holding rate gradually decreases (from 90% to 87%), and the liquid conduction rate also gradually decreases (from 12.5μL / s to 4.4μL / s). Therefore, the present invention can control the pore size, porosity, oil holding rate and liquid conduction rate of the atomizer core by controlling the gram weight and thickness of the atomizer core, thereby adjusting the performance of the atomizer core according to different usage requirements. Compared with Comparative Examples 1 to 6, the average pore size of the atomizer core in the present invention is smaller, and the pore size distribution is more concentrated. The particles of the aerosol after atomization using the atomizer core are smaller, and the aroma quality and aroma volume of the suction experience will have better performance. In addition, when the liquid supply is sufficient during suction, the risk of leakage is reduced. In addition, the liquid conduction rate of the atomizer core in the present invention is lower than that of Comparative Examples 1 to 6, which avoids the occurrence of oil frying caused by the small amount of smoke oil in the latter section, fast liquid conduction, and thickening of the oil film when the atomizer core is sucked in the latter section.
[0091] (1) X-axis and Y-axis liquid conduction performance test
[0092] Take 120g / m 2 , 160g / m 2 , 180g / m 2 , 200g / m 2 , 240g / m 2 , 280g / m 2 The atomizer cores (i.e., integrated cotton) in Examples 1 to 6 and the atomizer cores (i.e., non-woven fabrics) in Comparative Examples 1 to 6 of the same gram weight were then tested for their liquid conduction performance in the X-axis and Y-axis using the sessile drop diffusion method. The schematic diagram of the XYZ three-axis of the atomizer core is shown in FIG. Figure 6As shown, the specific test method is as follows: In order to make the evaluation results closer to the actual situation, the compression amount is considered during the test to evaluate the capillary capacity of the atomizer core, and a test device that can adjust the installation spacing of the atomizer core is designed. The structural diagram of the test device is shown in Figure 7 Shown and Figure 8 As shown, Figure 7 The overall structure diagram of the test device is shown in Figure 2. Figure 8 This is a schematic diagram of the structure of the transparent upper plate and the transparent lower plate of the test device. The transparent upper plate is provided with a dripping hole, and the transparent lower plate is provided with an air hole. The test device can adjust the compression amount of the atomizer core, and the thickness of the atomizer core can be compressed to 0.8mm, 0.9mm, and 1.0mm respectively. During the test, the atomizer core sample is first placed in the test device, the transparent upper plate and the transparent lower plate of the test device are fixed and locked by the locking piece, the compressed thickness of the atomizer core is adjusted, and then a fixed volume of 100μL of PG:VG with a volume ratio of 5:5 is dropped on the surface of the atomizer core (dripping from the dripping hole of the test device) by the sessile drop method, and the diffusion of the entire drop over time is photographed. The diffusion length of the X-axis and Y-axis over time is calculated by image processing software to evaluate the anisotropy of the capillary liquid conduction of the atomizer core. The specific test results are shown in Tables 3 and 4, respectively. Fig. 9 As shown:
[0093] Table 3 Test results of liquid conduction performance of the atomizer core in the X-axis and Y-axis directions in Examples 1 to 6 and Comparative Examples 1 to 6
[0094]
[0095]
[0096] Depend on Fig. 9As shown in Table 3, the liquid guide length of the atomizer core in the present invention differs by ≤0.6 mm in the X-axis and Y-axis. After being compressed to 0.8 mm, 0.9 mm, and 1.0 mm, the difference in the liquid guide length is <4.3%, indicating that the atomizer core in the present invention is a three-dimensional porous integrated structure formed by interweaving cotton fibers with a length of 5 to 13 mm. This structure has good structural stability and dimensional stability. The cotton fibers are randomly and evenly distributed in the X-axis and Y-axis directions without a fixed orientation. Therefore, the structural difference of the atomizer core in the X-axis and Y-axis directions is small, the liquid guide in the X-axis and Y-axis is uniform, and the droplets diffuse in a circular shape when diffusing in the X-axis and Y-axis. However, as the gram weight of the atomizer core increases, its diffusion area shows a decreasing trend, that is, the liquid guide rate decreases; under the same gram weight conditions, the smaller the thickness of the atomizer core, the greater the fiber density, the smaller the diffusion area, and the lower the liquid guide rate. The atomizing core in Comparative Examples 1 to 6 is made of spunlace nonwoven fabrics that are stacked, pressed, and cut. The warp and weft of the spunlace nonwoven fabrics are used to distinguish the spinning direction of the nonwoven fabric and the placement direction of the machine cloth. The warp refers to the spinning direction of the nonwoven fibers in the spunlace nonwoven fabric machine, that is, the longitudinal arrangement direction of the fibers; the weft refers to the transverse arrangement direction of the nonwoven fibers. In Comparative Examples 1 to 6 of the present invention, the fiber diameter is arranged in the X direction and the weft is arranged in the Y direction. The liquid guide length difference between the X-axis and the Y-axis is ≥1.8mm. After being compressed to 0.8mm, 0.9mm, and 1.0mm, the difference in the liquid guide length is >13.1%. The main reasons for the difference are the following three: (1) Different fiber orientations: In the manufacturing process of spunlace nonwoven fabrics, fibers are usually placed more along the warp direction and relatively less along the weft direction. Since the fibers are denser in the warp direction, water or liquid is more likely to penetrate and conduct along the warp direction. (2) Fiber interweaving structure: Spunlace nonwoven fabrics are formed by interweaving fibers together through the impact of high-pressure water columns, forming a three-dimensional interwoven structure. In the warp direction, the fibers are more crossed and connected, forming more channels and gaps, which facilitate the penetration and conduction of water or liquid.
[0097] (3) Difference in fiber arrangement density: The fibers in the warp direction are arranged more closely and have a higher fiber density, so more tiny pores or channels are formed between the fibers, which is conducive to the penetration and flow of water or liquid. However, the fiber density in the weft direction is lower, with fewer pores, which is relatively difficult to penetrate.
[0098] (2) X-axis and Z-axis liquid conduction performance test
[0099] According to the preparation method of the atomizer core in Examples 1 to 6 and Comparative Examples 1 to 6, a piece of one-piece cotton with a thickness of 2 cm was prepared and cut into a size of 2 cm*2 cm*2 cm. During the test, the X-axis and Z-axis directions were faced upward, and the sessile drop diffusion method was used to measure the liquid conduction performance of the atomizer core in Examples 1 to 6 and Comparative Examples 1 to 6 in the X-axis and Z-axis directions. The specific test method refers to the test method recorded in the X-axis and Y-axis liquid conduction performance test. The specific test results are shown in Tables 4 and Fig.10 As shown:
[0100] Table 4 Test results of liquid conduction performance of the atomizer core in the X-axis and Z-axis directions in Examples 1 to 6 and Comparative Examples 1 to 6
[0101]
[0102]
[0103] As can be seen from Table 4, the difference in the liquid conduction performance of the atomizer core in the XZ axis direction is greater than that of the XY axis. The reason is that when preparing the atomizer core, a wet molding structure is adopted. During the dehydration process, the cotton fibers are distributed more in the X-axis and Y-axis directions, and relatively less in the Z-axis direction, resulting in a large difference in the liquid conduction diffusion performance of the atomizer core in the XZ axis. The difference in the liquid conduction length between the X-axis and the Z-axis is less than 3.1 mm. After being compressed to 0.8 mm, 0.9 mm, and 1.0 mm, the difference in the liquid conduction length is less than 33%. Since the orientation of the cotton fibers of the atomizer core in the X-axis and Y-axis directions is randomly distributed, the difference in the liquid conduction between the X-axis and the Y-axis is very small. Therefore, the difference in the liquid conduction between the atomizer core in the Y-axis and the Z-axis is basically the same as the difference in the liquid conduction between the X-axis and the Z-axis. In contrast, the multilayer nonwoven fabrics in Comparative Examples 1 to 6 have the fastest liquid conduction speed because the X direction is the warp direction. In the Z direction, since multiple layers are stacked, a certain interlayer gap will be generated, which affects the liquid conduction performance, resulting in a large difference in the liquid conduction diffusion performance in the XZ axis. The liquid conduction length in the XZ axis direction differs by more than 4.2 mm. After being compressed to 0.8 mm, 0.9 mm, and 1.0 mm, the difference in the liquid conduction length is more than 27%.
[0104] (3) Y-axis and Z-axis liquid conduction performance test
[0105] Referring to the test method described in the XY axis liquid conduction performance test of the atomizer core, the liquid conduction performance of the atomizer core in Examples 1 to 6 and Comparative Examples 1 to 6 in the Y axis and Z axis were tested respectively. The specific test results are shown in Tables 5 and Fig.11 shown.
[0106] Table 5 Test results of liquid conduction performance of the atomizer core in the Y-axis and Z-axis directions in Examples 1 to 6 and Comparative Examples 1 to 6
[0107]
[0108]
[0109] As can be seen from Table 5, the difference in the liquid conduction performance of the atomizer core in the YZ axis direction is very small compared to the difference in the liquid conduction performance of the XZ axis. The difference in the liquid conduction length between the Y axis and the Z axis is less than 3.2 mm. After being compressed to 0.8 mm, 0.9 mm, and 1.0 mm, the difference in the liquid conduction length is less than 37%. Since the cotton fibers of the atomizer core are randomly oriented in the X-axis and Y-axis directions, the difference in liquid conduction between the X-axis and the Y-axis is very small. Therefore, the difference in liquid conduction between the atomizer core in the Y-axis and the Z-axis is basically the same as the difference in liquid conduction between the X-axis and the Z-axis. In Comparative Examples 1 to 6, the atomizer cores have a slower liquid guiding speed than that in the X direction because the Y direction is the latitude direction. In the Z direction, there will be a certain gap between the layers due to the multi-layer stacking, which affects the liquid guiding performance, resulting in the liquid guiding diffusion performance in the YZ axis being smaller than that in the XZ axis. The liquid guiding length difference in the YZ axis direction is greater than 3.7 mm. After being compressed to 0.8 mm, 0.9 mm, and 1.0 mm, the difference in the liquid guiding length is greater than 21%.
[0110] (4) Thermal conductivity test of X-axis, Y-axis and Z-axis
[0111] The heat absorbed or released by 1g of cotton fiber when the temperature changes by 1℃ is called the specific heat capacity of cotton fiber. The legal unit of measurement in my country is J / (g℃), and cal / (g℃) is a non-fixed unit of measurement. At 20℃, the specific heat capacity of dry cotton fiber is 11213~11339J / (g℃); the specific heat capacity of water is 41184J / (g℃), which is about 3 times that of cotton fiber. Therefore, the specific heat capacity of cotton fiber increases accordingly after absorbing moisture.
[0112] There are pores inside and between fibers, and these pores are filled with air. When the air does not flow, cotton fiber is a poor conductor of heat and has poor thermal conductivity. At a temperature of 26°C, the thermal conductivity (thermal conductivity) of cotton fiber is measured to be 0.071-0.073W / (m°C), the thermal conductivity of air is 0.026W / (m°C), and the thermal conductivity of water is 0.599W / (m°C). Therefore, as the moisture content of cotton fiber increases, its thermal conductivity increases and its warmth retention decreases. At high or low temperatures, the physical and chemical properties of cotton fiber will change.
[0113] The transient plane heat source method is to attach a probe to the specimen, and then calculate the thermal conductivity of the material by fitting the response of the sample surface temperature through a multivariate function; it is based on the transient temperature response of a disk-shaped heat source generated by step heating in an infinite medium. A plane probe is made of thermal resistance material, which serves as a heat source and temperature sensor at the same time. During the test, the probe is placed in the middle for testing. When the current passes through, a certain temperature rise is generated, and the generated heat diffuses to the samples on both sides of the probe at the same time. The speed of heat diffusion depends on the thermal conductivity characteristics of the material. By recording the relationship between the temperature and the response of the probe, the thermal conductivity and thermal diffusivity can be directly obtained from the mathematical model.
[0114] The thermal conductivity of porous materials is mainly related to the following parameters:
[0115] (a) Porosity of materials: Porosity refers to the ratio of the volume of voids in a material to its total volume. The larger the porosity, the smaller the proportion of effective medium in the material, which will reduce the thermal conductivity.
[0116] (b) Pore size and pore shape of the material: Pore size and pore shape will also affect the thermal conductivity. Generally speaking, the smaller the pore size and the more regular the pore shape, the smaller the thermal conductivity.
[0117] (c) Thermal conductivity and specific heat of materials: The thermal conductivity and specific heat of the material itself will also affect the thermal conductivity coefficient. Larger thermal conductivity and specific heat will affect the heat transfer results.
[0118] (d) Material density: The greater the density, the more media will collide with each other and transfer heat, thus causing more interference to the heat transfer, and will also affect the thermal conductivity.
[0119] (e): The greater the density, the more media will collide with each other and transfer heat, thus causing more interference to the heat transfer and also affecting the change of thermal conductivity.
[0120] Referring to the preparation method of the atomizer core in Examples 1 to 6, the weights of the atomizer cores were 140 g / m 2 , 160g / m 2 , 180g / m 2 , 200g / m 2 , 220g / m 2 , 240g / m 2 , 260g / m 2 , 280g / m 2 , 300g / m 2 The atomizer core body is then prepared by referring to the preparation method of the atomizer core body in Comparative Examples 1 to 6 to obtain atomizer core bodies with a gram weight of 140 g / m 2 , 160g / m 2, 180g / m 2 , 200g / m 2 , 220g / m 2 , 240g / m 2 , 260g / m 2 , 280g / m 2 , 300g / m 2 The atomizer cores are used as comparison; the atomizer cores are then compressed to a fixed thickness, and the specific thickness of the atomizer cores is shown in Table 6. Then, the thermal conductivity of the atomizer cores is tested by the transient plane heat source method. The specific test results are shown in Table 6 below:
[0121] Table 6 Thermal conductivity test results of the atomizer core in the X-axis, Y-axis and Z-axis
[0122]
[0123] It can be seen from Table 6 that the thermal conductivity of the atomizer core (i.e., integrated cotton) in the present invention differs by less than 6% between the X-axis and the Y-axis, while the thermal conductivity difference between the X-axis and the Z-axis and the thermal conductivity difference between the Y-axis and the Z-axis are both less than 20%. The reason is that the atomizer core is formed by an integrated wet method of cotton fibers, and the sedimentation and wet pressure of the fibers during the dehydration process cause the fiber density in the Z-axis to increase and the porosity in the Z-axis to decrease, thereby increasing the thermal conductivity of the Z-axis compared to the XY-axis. In contrast, the atomizer core (multi-layer non-woven fabric) adopts the spunlace process to form horizontal and vertical stripes. The fiber density of the horizontal stripes is usually greater than that of the vertical stripes. Therefore, the thermal conductivity difference between the X-axis and the Y-axis is relatively large, ranging from 20.00 to 23.44%, which is less than 24%; the thermal conductivity difference between the Y-axis and the Z-axis is relatively small, ranging from 7.41 to 13.33%, which is less than 14%. The reason is that the small density of the vertical stripes and the superposition of multiple layers of non-woven fabrics in the Z-axis direction will form a certain interlayer gap, which will lead to a reduction in the difference between the Y-axis and the Z-axis.
[0124] (5) Pore size and pore size distribution test
[0125] The pore size and pore size distribution of the atomizer core in Example 1 and Comparative Example 1 were tested by bubble pressure method. The specific test results are as follows: Fig.12 (a) and Fig.12 As shown in (b), Fig.12 It can be seen that the pore size of the atomizer core prepared in Example 1 is mainly distributed in 13-16 μm, with only one range of pore size distribution; while the atomizer core in Comparative Example 1 has a pore size distribution in three ranges, indicating that the pore size distribution of the core made of stacked non-woven fabrics is uneven, while the pore size distribution of the atomizer core prepared by wet integrated molding in the present invention is uniform.
[0126] Referring to the preparation method of the atomizer core in Examples 1 to 6, the weights of the atomizer cores were 140 g / m 2, 160g / m 2 , 180g / m 2 , 200g / m 2 , 220g / m 2 , 240g / m 2 , 260g / m 2 , 280g / m 2 , 300g / m 2 Referring to the preparation method of the atomizer core in Comparative Examples 1 to 6, the weights of the atomizer cores were 140 g / m 2 , 160g / m 2 , 180g / m 2 , 200g / m 2 , 220g / m 2 , 240g / m 2 , 260g / m 2 , 280g / m 2 , 300g / m 2 The atomizer cores were used as comparison; they were then compressed to a fixed thickness, and the specific thickness of the atomizer cores is shown in Table 7. Then, the bubble pressure method was used to test the pore size and pore size distribution of the atomizer cores. The specific test results are shown in Table 7 below, where a is the minimum pore size of D90, and b is the maximum pore size of D90.
[0127] Table 7 Atomizer core pore size and pore size distribution test results
[0128]
[0129] It can be seen from Table 7 that compared with the multi-layer non-woven atomizer core in Comparative Example 1, the length of the fiber used in the atomizer core of the present invention is 5-13 mm. Due to the short fiber length, the cross and interweaving between the fibers during molding are reduced, and the fibers are evenly dispersed and the fibers are arranged more closely; in addition, the wet molding and the interaction between the fibers make it easy for the fibers to gather together, which is also conducive to forming a more concentrated pore distribution. The ba≤3.1μm of the atomizer cores of different gram weights in the present invention further shows that the pore size distribution of the atomizer core in the present invention is uniform. The raw material used for the atomizer core in Comparative Example 1 is longer cotton fiber, the fiber arrangement is irregular, the fibers are crossed, interwoven, and twisted more often, and the difference in fiber length and diameter, the increase in fiber length makes it difficult to disperse evenly. In addition, due to the use of a stacking method during production, the interlayer gap causes incomplete contact between the fibers, which also affects the pore size and the unevenness of the pore size distribution. The ba value of the atomizer core in Comparative Example 1 with different gram weights is: 22.6μm≤ba≤25.3μm, which is significantly greater than the ba value in Example 1.
[0130] The atomizer core of the present invention is installed in an atomizer device for use, which can avoid the problems of core sticking, oil leakage, oil explosion, etc., and the particle size of the aerosol particles formed by atomization is more uniform, the suction effect and taste are better, and there is no taste attenuation problem.
[0131] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An atomizing core, characterized in that: The atomizing core is an interwoven integrated structure formed by forming a slurry containing short fibers, and the atomizing core meets at least one of the following characteristics: (1) The difference in liquid conduction rate between the atomizer core in the X-axis and the Y-axis is less than 10%, and the difference in liquid conduction rate between the atomizer core in the X / Y-axis and the Z-axis is less than 25%; (2) The difference in thermal conductivity between the atomizer core in the X-axis and the Y-axis is less than 10%, and the difference in thermal conductivity between the atomizer core in the X / Y-axis and the Z-axis is less than 20%; (3) 90% of the pore size of the atomizing core is φ, a≤φ≤b, 5 μm <a<45μm,5μm<b<45μm,b-a≤5μm。 2. The atomizer core according to claim 1, characterized in that: The atomizer core meets at least one of the following characteristics: (1) The difference in liquid conduction rate between the atomizer core in the X-axis and the Y-axis is less than 5%, and the difference in liquid conduction rate between the atomizer core in the X / Y-axis and the Z-axis is less than 25%; (2) The difference in thermal conductivity between the atomizer core in the X-axis and the Y-axis is less than 6%, and the difference in thermal conductivity between the atomizer core in the X / Y-axis and the Z-axis is less than 20%; (3) 90% of the pore size of the atomizing core is φ, a≤φ≤b, 5 μm <a<45μm,5μm<b<45μm,b-a≤4μm。 3. The atomizer core according to claim 1, characterized in that: The length of the short fibers is 5 to 13 mm; and / or the diameter of the short fibers is 10 to 30 μm; and / or the surface of the short fibers is distributed with fiber filaments with a diameter of 0.01 to 0.5 μm formed by brooming.
4. The atomizer core according to claim 1, characterized in that: The liquid conduction rate of the atomizer core is 4 to 15 μL / s; and / or the thermal conductivity of the atomizer core is 0.06 to 0.09 Wm -1 .K -1 ; and / or, the oil holding rate of the atomizer core is 62-92%; and / or, the moisture regain of the atomizer core is 600-950%; and / or, the fiber density of the atomizer core is 50-400 kg / m 3 .
5. The atomizer core according to claim 1, characterized in that: The porosity of the atomizer core is 60-93%; and / or the pore size of the atomizer core is 5-100 μm.
6. The atomizer core according to claim 1, characterized in that: The D90 value of the atomizing core is 10.9-16.3 μm.
7. The method for preparing the atomizer core according to any one of claims 1 to 6, characterized in that: The following steps are involved: The short fibers are beaten, then formed into sheets, and then wet pressed, dried, and dry pressed in sequence to obtain the atomizing core.
8. The method for preparing the atomizer core according to claim 7, characterized in that: In the beating step, the beating pressure is 0.4-0.6 MPa; the beating speed frequency is 35-45 Hz; and the beating degree is 25-26 degrees.
9. An atomizing device, characterized in that: It comprises the atomizing core body as described in any one of claims 1 to 6.
10. Use of the atomizer core according to any one of claims 1 to 6 in the field of electronic atomization.